UJI DAYA HAMBAT EKSTRAK ETANOL DAUN PANDAN HUTAN (Freycinetia sessiliflora Rizki) TERHADAP JAMUR Trichophyton mentagrophytes SECARA IN VITRO - Fitri Sri Rizki; Dzulyani Azzahra (Jurnal Komunitas Farmasi Nasional, 2021)
Pandan forests (Freycinetia sessiliflora Rizki) are among the species discovered in 2015 on mount passi West Borneo. Researchers found new pandan species very different from other pandan. The juxduring of pandan wood leaf fitycinetia's sesucleary of rizki's leaves contains skunder metabolic compounds of alkaloid, flavonoid, slamoid - steroids, saponin, fenol, and tannin. Based on the secondary metabolite compounds contained, a study was conducted to test the inhibition of the pandan extract with the fungus Trichophyton mentagrophytes. The extract of the pandan plant was obtained using a maseration method with a ethanol solot, which was obtained a thick extract that will be used to test the resistance against the fungus Trichophyton mentagrophytes it was agrophytes using the disk disk diffusion method (kirby&bauer test). Pandan extract is made in four different concentrations: 5%, 10%, 15%, and 20%. Then there was a clear zone measurement that formed around the disk paper. The data is analyzed by tabulation (chart) and described in a descriptive way.